Designing through Planetary Breakdown Locating Material Knowledge and Practical Skill - Carr, Chantel; Carr, Chantel; Stein, Jesse Adams (Taylor & Francis Routledge [Imprint], 2025)
In an era of profound environmental and geopolitical uncertainty, Designing through Planetary Breakdown offers fresh perspectives on design's evolving role in the face of planetary change. This unique collection emphasises practices and perspectives at the edges of conventional design, encompassing craft, material knowledge, repair, manual skills, creative practice and non-professional design, to reveal how design can address urgent challenges in grounded, hands-on ways. Structured into two sections - Skills and Capacities, and Care and Generative Practices - the chapters cover a rich range of topics examining both traditional and emerging approaches to making, caring and maintaining. Readers will find reflections on community-led adaptive urban heat strategies in Western Sydney, First Nations' perspectives on design labour, repair-led design education initiatives, and the ethical and social dimensions of global supply chains. The book journeys through a wide range of empirical examples, including from Cuba, Indonesia, Spain and Australia, offering insights into generative transformations of materials and technologies. It demonstrates how design, expanded beyond the traditional professional confines, can foster practical responses to global issues. Designing through Planetary Breakdown is ideal for scholars, students, designers and craftspeople across design studies, design anthropology, repair and discard studies, craft studies and more broadly in the humanities and social sciences. Practical and deeply social, this collection offers a call to action: a guide for all hands to shape a future not just of survival, but of regeneration and collective action. The Introduction and Chapter 3 of this book is freely available as a downloadable Open Access PDF at http://www.taylorfrancis.com under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC BY-NC-ND)] 4.0 license.
eng
Keywords: Design, Industrial and commercial arts, illustration; Development economics and emerging economies; Economics, Finance, Business and Management; Economics; Product design; The Arts; Climate change; Craft; Design education; Economies of design; Materials; Repair; Responsible design; Supply chains; Sustainable design